If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 = 2x + 3x + -10 Reorder the terms: 65 = -10 + 2x + 3x Combine like terms: 2x + 3x = 5x 65 = -10 + 5x Solving 65 = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 65 + -5x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 65 + -5x = -10 + 0 65 + -5x = -10 Add '-65' to each side of the equation. 65 + -65 + -5x = -10 + -65 Combine like terms: 65 + -65 = 0 0 + -5x = -10 + -65 -5x = -10 + -65 Combine like terms: -10 + -65 = -75 -5x = -75 Divide each side by '-5'. x = 15 Simplifying x = 15
| 6n=1+4n+19 | | 2sec^2x=3-tanx | | 3-21y-24y^2=0 | | X/2=2x-1/3 | | 30x/5+15x/3=15 | | -r^3t-rt^3=0 | | 3x^2-6y=0 | | 5=7x+3 | | 5x+30=20 | | 14x^2+33x+10=0 | | 24=18/x | | 14b-10= | | -5x+40=6x-60 | | 2(10)=24-2(10) | | -4=4v | | 88=x+x-6 | | -x=-77 | | X+2x-5=0 | | 10=24-2(10) | | 3f=-3+12 | | x+x-6=88 | | 400=0.14+2 | | x-6+x=88 | | 6x/3+7/15x+3 | | (x-8)/(-x+77)=2 | | 5(x+3)=-5 | | y=42+-5y | | -1.14*23.25+47= | | y=0.63(0.5)x | | 3/8x-8=-7 | | -.71*23.25+37= | | 8x^3=(-64) |